2017
DOI: 10.1155/2017/6481367
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Variation of Charcot-Marie-Tooth 1A in a Large Chinese Cohort

Abstract: Charcot-Marie-Tooth 1A (CMT1A) caused by peripheral myelin protein 22 (PMP22) gene duplication is the most common form of hereditary polyneuropathy. Twenty-four genetically confirmed CMT1A patients with sural nerve biopsies were enrolled in this study. The clinical picture included a great variability of phenotype with mean onset age of 22.2 ± 14.5 years (1–55 years). Pathologically, we observed a severe reduction in myelinated fiber density showing three types of changes: pure onion bulb formation in 3 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(27 reference statements)
0
5
0
2
Order By: Relevance
“…Some literature reviews and studies conducted on European and American CMT patients reveal the onset age of CMT1A is most frequently in the first decade of life . A Chinese study performed by Wu et al demonstrated an average onset age was 22.2 ± 14.5 years (ranged from 1 to 55 years) . A Japanese study showed half of the patients with CMT1A presented an age at onset after 20 years old .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some literature reviews and studies conducted on European and American CMT patients reveal the onset age of CMT1A is most frequently in the first decade of life . A Chinese study performed by Wu et al demonstrated an average onset age was 22.2 ± 14.5 years (ranged from 1 to 55 years) . A Japanese study showed half of the patients with CMT1A presented an age at onset after 20 years old .…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of ICMT was remarkable higher than the several previous studies, such as 2.4% in a Norwegian study 37 and 6.5% in a French study. 38 42 A Japanese study showed half of the patients with CMT1A presented an age at onset after 20 years old. 25 In our study, the median age of onset in CMT1A patients was 32.5 years old, which may indicate patients with PMP22 duplication in southeast China have milder symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Duplication of the PMP22 gene most commonly causes demyelinating Charcot‐Marie‐Tooth disease type 1A (CMT1A), which accounts for 20–64% of all patients with CMT. Patients usually present with slowly progressive length‐dependent neuropathy with pes cavus . Deletion of PMP22 causes hereditary neuropathy with liability to pressure palsies (HNPP).…”
Section: Introductionmentioning
confidence: 99%
“…О.О. Богомольця НАН України, Київ; e-mail: tsupykov@gmail.com 3 ННЦ «Інститут біології та медицини» Київського національного університету імені Тараса Шевченка; 4 ДУ «Інститут генетичної та регенеративної медицини Національної академії медичних наук України», Київ; 5 ДУ «Інститут геронтології ім. Д. Ф. Чеботарьова Національної академії медичних наук України», Київ У роботі досліджували демієлінізацію у трансгенних мишей з периферичною нейропатією та вплив трансплантації мультипотентних мезенхімальних стромальних клітин (ММСК) жирової тканини на ультраструктурні особливості сідничого нерва цих мишей.…”
unclassified